The scientific method in tourism education: Research experience at the Autonomous University of Ciudad Juarez, Mexico - González Herrera, Manuel Ramón (USF M3 Publishing, 2021)
The general aim of this investigation was developing a research experience as a training process that favors the construction and validation of a conceptual model with the stages of the scientific method through a case study with tourism students. A theoretical - applied, qualitative, interdisciplinary and deductive research type was implemented, in which mixed data sources were used, and methods like literature review, observation, triangulation, modeling, case study, and empirical validation were implemented. The main outcomes were the construction of the conceptual scientific model, validation of the model by its implementation in an empirical case study, and identification of learning lessons as opportunities for the replication of the scientific model. As a conclusion, the correspondence between the implemented scientific model and the reality where students developed their projects is recognized.